Environmental management systems: analysis of the degree of maturity of companies in the Rio Grande port complex - Fontoura, Daiane Gonçalves da; Bonato, Samuel Vinícius; Junges, Vanessa de Campos; Salomão, Catherine Santos (Revista de Administração da UFSM, 2025)
Purpose: Analyze the maturity levels of the environmental management system of private sector companies in the port of Rio Grande. Methodology: As a method, this study applied a mixed quantitative and qualitative research approach. The method included multiple case studies in two companies, evaluated based on an instrument developed by Peixe (2014), which measures the maturity of EMSs on a five-level scale, ranging from reactive initiatives to formalized proactive practices. Findings: The findings indicate that both companies are in the "Proactive Initiative" stage, showing significant commitment to formal environmental practices, but without reaching the "Proactive" stage, in which all actions are fully implemented. Research limitations: Limitations of the study include the small number of companies and the reliance on self-reporting, which may compromise the objectivity of the data. Furthermore, the methodology could benefit from the inclusion of more detailed qualitative analysis, such as interviews with environmental managers. Originality/value: This work is original because it adapts and applies an environmental maturity methodology specific to the Brazilian port context, providing a detailed view of the progress of sustainable practices in this sector. The research contributes by demonstrating the importance of EMS for environmental sustainability and offers managerial insights to improve the integration between environmental and operational practices.